The Influence of Halal Product Certification and Price on Cosmetic Purchasing Decisions in Student FEBI IAIN Fattahul Muluk Papua - Ana ’Arifah; M. Anang Firdaus; Wira Kafryawan (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
The main problem in this study is that there are still many cosmetic products that have not been halal certified and the purchasing power of female students for cosmetic products is quite high, in other words can halal certification have a significant influence on cosmetic purchasing decisions for female students of FEBI IAIN Fattahul Muluk Papua. This study aims to determine the effect of halal product certification and prices on cosmetic buying decisions for female students of FEBI IAIN Fattahul Muluk Papua. The type of research used is quantitative research and the type of data used is primary data obtained from distributing questionnaires usingscale likert. The sampling method is obtained by techniquenon probability sampling. With the number of respondents 70 female students of FEBI IAIN Fattahul Muluk Papua based on the specified criteria/characteristics. The data analysis method used in this study is multiple linear regression. The results of this study indicate that Ha accepted and HO rejected. This means that there is a significant effect of halal product certification and prices both partially and simultaneously on the decision to purchase cosmetics for FEBI IAIN Fattahul Muluk Papuan students. This can be seen from the value of tcounthalal product certification variable is 3,550 > ttable 1996. And t valuecountprice variable of 12,253 > ttable 1996. In addition, the calculation results of fcountof 179,139 > ftable3.13, halal product certification and prices simultaneously have a significant effect on cosmetic purchasing decisions for FEBI IAIN Fattaul Muluk Papuan studen